Persepsi Masyarakat Kabupaten Rokan Hilir Terhadap Akuntabilitas Kepemimpinan Annas Maamun dan Suyatno Masa Bakti 2006-2014 - Mirzahan Pratama; Priyatno H; Lusia A (Journal of Politic and Government Studies, 2014)
ABSTRACT             The study is titled "Public Perception of Rokan Hilir Against Accountability Leadership Annas Maamun and Suyanto in period 2006-2014". This research is motivated by the problem of accountability and transparency is one of the problems in the implementation of local government, which until now kept under implementation by the government. To realize the government accountable to its citizens one way to use the principle of transparency (openness). Through the transparency of governance, public policy given the opportunity to know who will and have been taken by the government. (Quoted www.amin-rahmanurrasjid.blogspot.com).            Accountability according to Lawton and Rose: a process by which a person or group of persons required to make reports of their activities and the way they have or have not been known to carry out their work. Accountability as one of the good corporate governance principles related to leadership accountability for decisions and results achieved, in accordance with the delegated authority in the implementation of the responsibilities of managing the organization. (Quoted from Nico Andrianto, Transparency and Public Accountability through e-Government). Miftah Thoha (1990:4) gives the definition, perception of cognitive processes experienced by every person in understanding the information about its environment, either through sight, hearing, appreciation, feeling, smell. From the definition of Miftah Thoha seen that the human senses play an important role in the emergence of perception. The research method used is a survey research methods. Survey research by Singarimbun (1989:33), namely, the study took a sample of the population and the use of questionnaires as the main data collection tool.            Accountability the public perception of "Leadership Annas Maamun and Suyanto in the period served as Regent and Vice Regent of Rokan Hilir between 2009 s / d 2014". Based on the results of the study respondents, in terms of "Infrastructure (97%)", "Public Welfare (99%)", "Health (41%)", "Education (99%)", "Policy (96%)" the perception of the respondents stated that government accountability Rokan Hilir transparent. Keywords: Perception, Rokan Hilir, Accountability, Annas Maamun and Suyanto.